Pengaruh Debt To Equity Ratio, Working Capital Turnover, Fixed Asset Turnover Dan Gross Profit Margin Terhadap Tindakan Praktik Perataan Laba Pada PT. Global Maritim Industri - Cindy Seleste; Thomas Sumarsan Goh; Elidawati Elidawati; Edison Sagala (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The formulation of the problem in this study is the extent to which the influence of debt to equity ratio, working capital turnover, fixed asset turnover and gross profit margin on income smoothing practices at PT. Global Maritim Industri. The research method used in this research is a quantitative approach. The population in this study is the monthly financial statements of PT. Global Maritim Industri which consists of 48 financial statements for 2017 - 2020. The sampling method is purposive sampling, a sample of 40 financial reports per month PT. Global Maritim Industri. The data analysis model used to answer the hypothesis is multiple regression. The results showed that the debt to equity ratio, working capital turnover, fixed asset turnover and gross profit margin simultaneously had a simultaneous effect on income smoothing practices at PT. Global Maritim Industri. And partially working capital turnover and fixed asset turnover affect the practice of income smoothing at PT. Global Maritim Industri. However, debt to equity ratio and gross profit margin have no effect on income smoothing practices at PT. Global Maritim Industri. Keywords : Debt to equity ratio, Working capital turnover, Fixed asset turnover, Gross profit margin and Income Smoothing Practices